2014
DOI: 10.3389/fnhum.2014.00211
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during phonological and semantic processing of Chinese characters in deaf signers

Abstract: Previous studies found altered brain function in deaf individuals reading alphabetic orthographies. However, it is not known whether similar alterations of brain function are characteristic of non-alphabetic writing systems and whether alterations are specific to certain kinds of lexical tasks. Here we examined differences in brain activation between Chinese congenitally deaf individuals (CD) and hearing controls (HC) during character reading tasks requiring phonological and semantic judgments. For both tasks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…However, these differences were only evident in region of interest (ROI) analyses -not in the whole-brain analysis. Li, Peng, Lui, Booth, and Ding (2014) found a similar (and statistically more robust) pattern for deaf Chinese readers making semantic relatedness judgments to pairs of Chinese characters. The deaf readers (fluent users of Chinese Sign Language) showed greater activation in right frontal cortex (as well as in the right inferior parietal lobule) and reduced activation in left IFG compared to hearing readers (reading ability was not assessed).…”
mentioning
confidence: 62%
“…However, these differences were only evident in region of interest (ROI) analyses -not in the whole-brain analysis. Li, Peng, Lui, Booth, and Ding (2014) found a similar (and statistically more robust) pattern for deaf Chinese readers making semantic relatedness judgments to pairs of Chinese characters. The deaf readers (fluent users of Chinese Sign Language) showed greater activation in right frontal cortex (as well as in the right inferior parietal lobule) and reduced activation in left IFG compared to hearing readers (reading ability was not assessed).…”
mentioning
confidence: 62%
“…For example, deaf readers can take in more information in the parafoveal visual range (i.e., the parafovea, which encompasses one to two words beyond the fixated word for most readers—see Vasilev & Angele, 2017) and process it more efficiently than hearing readers (Bélanger et al, 2012, 2013, 2018; Yan et al, 2015). Despite having limited access to spoken phonology, there is evidence that deaf readers activate phonological code during silent reading (Gutierrez-Sigut et al, 2017; Hanson & Lichtenstein, 1990; Li et al, 2014; Yan et al, 2015). Elliott et al (2012) suggested that those phonological units, rather than being based on acoustic information, are based on mouth-shape-based units acquired through lip-reading.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, because of the informational challenges to the cerebral cortex, non-native Chinese speakers are more likely to feel mental exhaustion when reading and comprehending Chinese Some researchers find comprehension is a little different in Chinese rhyme readings. Li et al (2014) detected that when comprehending Chinese rhyme readings, the right middle frontal gyrus in the cortex is more active. The right middle frontal gyrus, as Japee et al (2015) explain, influences the control of reorienting attention from external factors.…”
Section: Cognitive Process and Chinese Reading Comprehensionmentioning
confidence: 99%